Pengetahuan, Sikap, Respons Perilaku Adaptasi, Dukungan Suami serta Kondisi Depresi Ibu Hamil Remaja - Kusuma, Ratu; Armina, Armina; Sari, Mila Triana; Hesty, Hesty; Nurita, Suci Rahmani (Jurnal Akademika Baiturrahim Jambi, 2025)
Putri Ayu Community Health Center is one of the community health centers in Jambi City with a relatively high rate of teenage pregnancies. Over the past five years (2020-2024), there were 164 teenage pregnancies. In 2020 (33 cases), 2021 (33 cases), 2022 (35 cases), 2023 (31 cases), and 2024 (32 cases), eight of these pregnancies involved girls aged 14-15 years. In addition, interviews were conducted with 2 teenage mothers. Both mothers showed symptoms of depression such as lack of communication with other people, including biological mothers and health workers; locking yourself up in your room for several days without interacting with your children and other family members; refusing to eat and rarely bathing and not complying with the advice of health workers. When interviewed, the mother looked pale, her clothes and body were dirty. This study is a descriptive study of 32 teenage pregnant women in the working area of ​​the Putri Ayu Community Health Center who were selected by accident. The aim is to identify knowledge, attitudes, adaptive behavioral responses, husband's support and depression conditions of teenage pregnant women using the EPDS-10 instrument. Filling out the questionnaire was carried out on 07 December 2023-10 June 2024, while additional information was collected by telephone 1-2 times to teenage mothers who showed symptoms of depression, then the data was analyzed univariately. A total of 19 (59.37%) mothers had poor knowledge about teenage pregnancy, 15 (46.88%) mothers agreed with teenage pregnancy, 34.38% responded non-adaptively, 15 (46.88%) received less support both husbands and 3 mothers (9,38%) experienced depression. It was concluded that teenage mothers had poor attitudes towards teenage pregnancies, lacked support from their husbands and some even experienced depression.